Three new species of the genera Loxoconcha and Xestoleberis (Crustacea, Ostracoda, Podocopida) from central and southern Vietnam - Dung, Le Doan; Tsukagoshi, Akira (Zootaxa, 2018)
The present study reports three new species of Ostracoda, Loxoconcha damensis sp. nov., Xestoleberis vietnamensis sp. nov. and X. munensis sp. nov., from Phu Quoc Island, southwest Vietnam and Nha Trang Bay, central Vietnam. These species inhabit the coral reefs around isolated islands and can be easily distinguished from other known species based on their morphological differences, mainly in the male copulatory organ. Loxoconcha damensis sp. nov. belongs to Loxoconcha Group A, based on the distributional pattern of their pore system below the eye tubercle. Similarly, based on a combination of morphological types of pore systems, the two new Xestoleberis species belong to Xestoleberis Group A, because these species have two types of pore systems, i.e., sieve-type and lip-type. To the best of our knowledge, this study is the first report on Xestoleberididae and the second on Loxoconchidae from the Recent of Vietnam.